REPRESENTASI GAGASAN FEMINISME DALAM FILM THE HUNGER GAMES - Anissa Karamina Viandra (Communicare : Journal of Communication Studies, 2016)
This research discusses about the idea of feminism in the film The Hunger Games. Feminism is generally understood as a movement that asks for the equality of rights between women and men. The idea of feminism in the film is shown by the main character, Katniss Everdeen. By employing Hartsock’s standpoint theory, the research attempts to uncover how the idea of feminism in the film The Hunger Games is represented. The research is a qualitative study by analyzing data from selected scenes of The Hunger Games. It is concluded that the film The Hunger Games contains the idea of feminism that is in accordance with Hartsock’s standpoint theory and the third wave feminism (which is Postmodern feminism). Keywords: film, The Hunger Games, representation, feminism Penelitian ini membahas tentang gagasan feminisme dalam film The Hunger Games. Feminisme secara umum dipahami sebagai gerakan yang menuntut persamaan hak antara kaum wanita dan pria. Gagasan feminisme dalam film ini diperlihatkan oleh karakter utama yaitu Katniss Everdeen. Dengan menggunakan teori sikap Hartsock, penelitian ini berusaha mengungkapkan bagaimana gagasan feminisme di dalam film The Hunger Games direpresentasikan. Penelitian ini adalah penelitian kualitatif dengan menganalisa data dari adegan-adegan terpilih film The Hunger Games. Berdasarkan hasil penelitian, film The Hunger Games mengandung gagasan feminisme yang sesuai dengan teori sikap Hartsock dan feminisme gelombang ketiga (yaitu feminisme Postmodern). Keywords: film, The Hunger Games, representasi, feminisme